PENINGKATAN PENGETAHUAN DAN PEMERIKSAAN TEKANAN DARAH SEBAGAI SKRINING HIPERTENSI - Trajanus L. Yembise; Herlambang Budi Mulyono (LPPM Uncen, 2022)
Hypertension is a silent killer where the symptoms can vary in each individual and are almost the same as the symptoms of other diseases. The purpose of this activity is to find out the increase in knowledge about hypertension and blood tests as a screening for hypertension. The service uses the lecture method on hypertension, direct examination of the respondent's blood pressure at the activity site. The results of the service show that the data from the blood pressure test found that three men aged over 40 years suffered from high blood pressure, each with a junior high school education level and two high school students. While the female sex as many as two people suffer from high blood pressure in college and junior high school. In addition, there was an increase in knowledge and there were several cases of high blood pressure or hypertension at the service location. The findings of these activities can be used as a reference or management of hypertension for sufferers so that they can reduce other adverse effects that accompany hypertension.Keywords: hypertension; symptoms; blood pressure; management; screening